Pharmacoeconomic aspects of the treatment of diabetic foot syndrome - Marina Fedorovna Kalashnikova; Nadezhda Viktorovna Maksimova; Oleg Viktorovich Udovichenko; Yury Ivanovich Suntsov (Сахарный диабет)
Treatment of patients with diabetic foot syndrome (DFS) is a major medico-social problem facing public health services. One of its important aspectsis high cost of the treatment. In connection with this, not only medical but also economic issues pertinent to DFS have recently been widely discussedin different countries. Clinico-economic analysis of the use of new medicinal products, therapeutic modalities, and established medical technologiesis of primary importance for making decisions concerning allocation of available financial resources. The present review of foreign publications focuseson the studies providing additional arguments in favour of modern efficacious methods for the management of DFS. The review is intended to motivateclinicians and health officials to revise current approaches to the treatment of DFS patients in this country.